CITRA PEREMPUAN DALAM NOVEL PEREMPUAN KEMBANG JEPUN KARYA LAN FANG - Oktasari, Anisa Fajriana (Kantor Bahasa Banten, 2020)
Peneliti tertarik meneliti masalah perempuan dalam novel karya Lan Fang, karena perempuan-perempuan yang ditampilkan dalam novel-novel karya Lan Fang memiliki bermacam kepribadian. Bermacam kepribadian ini dilatarbelakangi oleh budaya atau latar yang berbeda-beda, antara lain Cina, Dayak, dan Jawa. Ketiga latar yang berbeda tersebut merupakan ciri dari pengarang Lan Fang sendiri. Peneliti mengambil novel yang berjudul Perempuan Kembang Jepun untuk mengetahui sejauh mana Lan Fang memandang dan menilai sosok perempuan dari sudut pandang Lan Fang sendiri. Penelitian ini memiliki rumusan masalah yaitu: bagaimanakah citra perempuan dalam novel Perempuan Kembang Jepun karya Lan Fang. Teori yang mendukung dalam penelitian ini adalah teori feminisme. Teori ini untuk menganalisis masalah tokoh perempuan dan perwatakannya, peran dan sikap tokoh perempuan, dan citra perempuan dalam kelima novel Perempuan Kembang Jepun karya Lan Fang tersebut. Tokoh perempuan yang digambarkan dalam penelitian ini banyak menggambarkan sosok perempuan modern yaitu mandiri, berpendidikan, berwawasan luas, memiliki pandangan tentang hidupnya. Di balik itu semua ada beberapa tokoh dalam novel karya Lan Fang yang memperlihatkan sosok perempuan tradisioanal dan bagaimana perempuan ini menyelesaikan perjalanan hidupnya dengan cara pandangnya sendiri. Citra perempuan yang ditampilkan dalam novel Perempuan Kembang Jepun karya Lan Fang banyak yang menekankan pada kehidupan mandiri dengan tetap memegang peranannya sebagai partner laki-laki, ada beberapa perlawanan di dalamnya dan sedikit kebencian terhadap laki-laki. Namun, terlihat jelas citra perempuan yang ditampilkan Lan Fang tetap pada koridor perempuan di belakang laki-laki.Kata kunci: citra perempuan, novel Lan Fang, feminisme.The writer is interested in observing the woman’s problem in Lan Fang’s novel. The women which are displayed in the se novels have various characters. it happens because of the different background of their cultures and settings such as China, it self Dayak, and Java. These are the uniqueness of Lan Fang her self. The writer take Lan Fang’s novel with the title Perempuan Kembang Jepun in order to find out Lan Fang judgement and point of view about woman. The writer has research question they are, how is the image in Lan Fang’s novels. The research is supported by feminism theory. The writer takes feminism theory from Tong and Ilyas, because it is the most appropriate to the Lan Fang’s novel. This theory is used to analyze the woman’s problem and her character, her attitude and her role as shows on Perempuan Kembang Jepun novel. The woman’s character which is described on this research take many description on the modern an ideal figure woman such as independence, educated, smart, has a view in her life. Beyond those explanation, there are some character on Lan Fang’s novels that show a traditional figure of woman and how woman get through, with own her point of view. Not only that, there figure are also a woman who hates men and vice versa, a woman who need men. The woman’s image which is showed on Perempuan Kembang Jepun described as beautiful woman, modern, and independence. Beside that there are some women which are despised them selves dignity. She overcomes suffering until she could reach her happiness. There is also a character who emphasized on independence life and keep holding on herrole as men’s partner, and vice versa. A character who against men, all of woman’s character from men needed until men hatred.Key Word: Women’s Image, Lan Fang’s novel, feminism